Hunters, fishers, traders – An archaeological and zooarchaeological perspective on the development of the Late Iron Age and medieval northern Fennoscandian trade network. - Jari-Matti Kuusela; Anna-Kaisa Salmi; Tiina Äikäs (Estonian Academy Publishers, 2021)
Late Iron Age and medieval trade in northern Fennoscandia has arguably often thought to have been primarily fur trade. However, recent discoveries of Late Iron Age and early medieval sites in the north together with the reexamination of previous evidence reveals a more nuanced picture and indicates that trade in bulk goods – namely inland stockfish and reindeer products – may have played a significant role in the northern trade. This article examines both archaeological and zooarchaeological evidence from several sites in northern Fennoscandia from the perspective of trade economy, and it is suggested that the northern trade began to flourish at the beginning of the Viking Age in the early 9th century and may have been driven by the demand of fish by the European markets. It is also suggested that at the beginning of the 13th century at the latest, the trade economic importance of reindeer became prominent and would increasingly remain so up until the historical period. The authors therefore suggest that although the role of furs in the northern trade was significant, reindeer hunting and inland fishing should also be considered to have been of major trade economic importance.